2017
DOI: 10.1016/j.ejvs.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Arch Catheter Placement Reduces Cerebral Embolization During Thoracic Endovascular Aortic Repair (TEVAR)

Abstract: Robotic catheter placement is feasible during TEVAR, and results in significantly less cerebral embolization compared with manual techniques. The active manoeuvrability, control, and stability of the robotic system is likely to reduce contact with an atheromatous aortic arch wall, and thereby reduce dislodgement of particulate matter and result in less embolization. The importance of adhering to manufacturer instructions during use and removal of the robotic catheter is also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 25 publications
0
17
0
3
Order By: Relevance
“…Robotic navigation has been shown to reduce contact with the aortic arch wall during TAVI, and to cause significantly less cerebral embolization compared with manual techniques during TEVAR due to the active manoeuvrability and stability of the robotic system 38,39 . A dynamic bubble trap designed to reduce gaseous emboli has been shown to reduce TCD HITS, and cognitive function 3 months after surgery was significantly better compared with that in control patients undergoing coronary artery bypass grafting 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Robotic navigation has been shown to reduce contact with the aortic arch wall during TAVI, and to cause significantly less cerebral embolization compared with manual techniques during TEVAR due to the active manoeuvrability and stability of the robotic system 38,39 . A dynamic bubble trap designed to reduce gaseous emboli has been shown to reduce TCD HITS, and cognitive function 3 months after surgery was significantly better compared with that in control patients undergoing coronary artery bypass grafting 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The maximum proportion of solid to gaseous emboli (13%) occurred during wire and pigtail manipulation. Perera et al 25 demonstrated a reduction in the number of HITSs with robotic catheter placement, and this technique could be explored to reduce embolization in this phase. The increase in DW-MRI lesion surface area (r s ¼ 0.928; P ¼ .01) with an increased number of solid HITSs (Fig 3, C), the association between a more diseased aortic arch and increased MRI lesion diameter ($3 mm; Fig 3, B), and the presence of embolic material captured within the filters, all support the hypothesis that solid particle embolization contributes to brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] 2015 Magellan 37 vessels Visceral and renal vessel cannulation during FEVAR/BEVAR Mahmud et al [ 42 ] 2016 CorPath 200 20 patients Percutaneous angioplasty of the SFA Perera et al . [ 43 ] 2017 Magellan 11 patients Catheter placement in aortic arch during TEVAR Cheung et al 2020 Magellan 14 patients EVAR gate cannulation Mahmud et al . [ 44 ] 2020 CorPath GRX 20 patients Percutaneous angioplasty of the SFA Sajja et al .…”
Section: Robot-assisted Endovascular Surgerymentioning
confidence: 99%
“…But up to date, in vivo experience in robotic-assisted endovascular aortic repair is limited to aortic arch catheter placement during TEVAR [ 43 ], contralateral gate cannulation in EVAR [ 51 ], and cannulations of renal or mesenteric arteries during FEVAR [ 52 ]. Manual intervention is still necessary, but with future technical progress and by combining the robot with three-dimensional fusion imaging technology, these challenging procedures may be performed with little radiation and contrast use, thus significantly improving patients’ safety as well as the surgeon’s radiation exposure.…”
Section: Robot-assisted Endovascular Surgerymentioning
confidence: 99%
See 1 more Smart Citation